Organizational spirituality and its implications for organizational performance: A survey of the opinions of employees of the General Company for Food Industries in Abu Ghraib (Baghdad) - ابراهيم, مها فاضل (Journal of Economics and Administrative Sciences, 2019)
The research discusses with organizational spirituality and its implications on the organizational performance in the General Company for Food Industries in Abu Ghraib (Baghdad). The aim of the research was to determine the contribution of organizational spirituality in the organizational performance of the surveyed company. In order to achieve the objectives of the research، two main hypotheses were adopted. Several sub-hypotheses centered on the relationship between organizational spirituality and organizational performance in terms of its dimensions (Meaning work، self-esteem، community affiliation، and the alignment of individual and organization values). The research was based on the analytical descriptive approach in presenting the data and discussing it by describing the situation by analyzing it and extracting its results. Using a set of statistical methods through the statistical program (SPSS)، the empirical data was analyzed، which included analyzing the answers of the 60 individuals interviewed in the company. As well as، the analysis of statistical relations between the variables of research، has been reached a set of conclusions، the most important to achieve a significant impact of organizational spirituality in organizational performance، which implies that the availability of organizational spirituality in the personnel working contributes to the performance High organizers in the company surveyed.